Pre-Ablation rhTSH-Stimulated F-18 FDG PET/CT Changes Patient Management in Increased-Risk Thyroid Cancer - Rendl, Gundula; Rettenbacher, Lukas; Schweighofer-Zwink, Gregor; Hehenwarter, Lukas; Pirich, Christian (Hormone and Metabolic Research, 2020)
The aim of the study was to evaluate the clinical impact of pre-ablation rhTSH-stimulated fluorine-18 fluorodeoxyglucose (F-18 FDG) PET/CT in addition to post-therapeutic whole body radioiodine scanning in patients with intermediate to high risk differentiated thyroid carcinoma (DTC). This was a retrospective single center study including 73 patients with thyroid cancer (44 females, mean age 43.2±16.2 years, 62% papillary, 31% follicular, 7% poorly differentiated). All patients underwent ablative radioiodine treatment (mean activity: 3661±673 MBq I-131) using rhTSH after thyroidectomy and lymph node (LN) dissection (01/2013–10/2016) and TSH-stimulated F-18 FDG PET/CT (4 MBq/kg body weight, low dose CT). Post-treatment I-131 whole body scan (I-131 WBS) was obtained 9 days afterwards in planar technique and in case of equivocal or abnormal findings using SPECT/CT. Thirty-one patients (42%) showed F-18 FDG avid lesions, 14 patients showed more FDG than iodine positive lesions and 5 patients more iodine positive lesions in I-131 WBS, respectively. Fifty-three patients showed identical F-18 FDG PET/CT and I-131 WBS. The initial treatment plan was changed from follow-up to therapy (surgery, systemic therapy using tyrosine-kinase inhibition) in 11 patients (15%) on the basis of F-18 FDG PET/CT imaging. Six of these 11 patients had papillary thyroid cancer. Three patients with histologically proven LN metastases had stimulated thyroglobulin-levels<2.0 ng/ml. Our study demonstrated a clinical benefit of pre-ablation rhTSH-stimulated F-18 FDG PET/CT imaging in about 20% of patients with intermediate to high risk DTC, leading to change in patient management in 15%.
Keywords: F-18 FDG PET/CT; differentiated thyroid cancer; radioiodine ablation; recombinant human TSH; thyroglobulin; whole-body radioiodine scan; increased-risk thyroid cancer